Hadith #2729 - Sahih Muslim - al-Sa'b bin Juthama bin Qays (Sahih Muslim)
When the Messenger of Allah (ﷺ) looked into my face (which had the mark of dejection as my present had been rejected by him) he (in order to console me) said: We have refused it only because we are in a state of Ihram.
Grade: Sahih

Hadith #4419 - Sahih Muslim - al-Sa'b bin Juthama bin Qays (Sahih Muslim)
What about the children of polytheists killed by the cavalry during the night raid? He said: They are from them.
Grade: Sahih